Blend the demand: Micro-breaks as a pathway to work engagement - Septiawan, Fajar Eryanto; Salsabil, Imanirrahma (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study examines the role of micro-breaks as a mediator between perceived job demand and work engagement. Additionally, it explores the moderating effect of micro-break climate to investigate whether a supportive work culture enhances or hinders employees’ ability to take effective breaks. Using a quantitative approach, survey data is collected from 228 startup employees across various roles. Structural equation modeling (SEM) is employed to analyze the relationships among perceived job demand, micro-breaks, micro-break climate, and work engagement. The findings indicate that high perceived job demand negatively affects work engagement. Additionally, perceived job demand can affect employees to take micro-breaks, while a positive micro-break climate could mitigate this effect by fostering a supportive environment for break-taking. Furthermore, a high micro-break climate strengthens the positive impact of micro-breaks on work engagement. This study extends the conservation of resources (COR) theory by demonstrating how micro-breaks serve as a recovery mechanism in high-demand work settings. It also highlights micro-break climate as boundary condition and contextual resource that shapes the effectiveness of micro-breaks. Organizations should cultivate a positive micro-break climate by encouraging short breaks without stigma. Such environment can help employees maintain engagement even under high job demands. Since this study is cross-sectional, future research should employ longitudinal designs to better understand the long-term effects of micro-breaks. Additionally, future studies could explore how these findings generalize to other industries with different job demands and workplace cultures.